ダイ 29 ジ ナンキョク チイキ カンソク タイ アスカ カンソク キョテン エットウ ホウコク 1988-1989 - 矢内, 桂三; ヤナイ, ケイゾウ; Yanai, Keizo (1990)
P(論文) 第29次観測隊あすか越冬隊の活動を報告する。あすか越冬隊は4名の研究者を含む10名で構成され, 1987年12月28日, 第28次観測隊からあすか観測拠点の管理運営を引き継いだ。あすか越冬隊の主要な観測計画はセールロンダーネ山地(Sor Rondane Mountains)における組織的な隕石探査であった。その他主な観測として, 気水圏研究, 気象観測の他超高層物理, 医学・生物, 雪氷, 寒地工学に関する調査研究も合わせて実施した。隕石探査は1988年1月から翌年の1月までの5回, 計150日に上る組織的な探査を行い, 約2000個の隕石を採集した。総重量は約400kgである。その他の研究観測もほぼ予定通り実施出来た。 The wintering activities at Asuka Station by the 29th Japanese Antarctic Research Expedition (JARE-29) are reported. The winter party at Asuka Station, (the Asuka party), consisted of 10 persons including four scientists. On December 28,1987,the Asuka party took over Asuka Station which was started by JARE-28 in February 1987,then continuously maintained the station during the wintering. The station was succeeded by JARE-30 on December 22,1988. The main scientific program of the Asuka party is the search for Antarctic meteorites on the bare ice around the Sor Rondane Mountains. Other programs comprised the meteorological surveys, studies of upper atmosphere physics, glaciological survey, medical-biological studies, and logistic survey of the housing at Asuka Station. A systematic search for Antarctic meteorites was carried out five times, between January 1988 and January 1989,amounting to about 150 days. More than 2000 meteorites, about 400 kg in weight, were collected from three main areas around the mountains. The other programs were also carried out successfully during the wintering. departmental bulletin paper